Abrupt changes in deep Atlantic circulation during the transition to full glacial conditions. (30th May 2013) - Thornalley, David J. R.; Barker, Stephen; Becker, Julia; Hall, Ian R.; Knorr, Gregor
Abstract : [1] Six Ocean Drilling Program (ODP) sites, in the Northwest Atlantic have been used to investigate kinematic and chemical changes in the "Western Boundary Undercurrent" (WBUC) during the development of full glacial conditions across the Marine Isotope Stage 5a/4 boundary ( 70, 000 years ago). Sortable silt mean grain size SS ¯ measurements are employed to examine changes in near bottom flow speeds, together with carbon isotopes measured in benthic foraminifera and % planktic foraminiferal fragmentation as proxies for changes in water‐mass chemistry. A depth transect of cores, spanning 1.8–4.6 km depth, allows changes in both the strength and depth of the WBUC to be constrained across millennial scale events. SS ¯ measurements reveal that the flow speed structure of the WBUC during warm intervals ("interstadials") was comparable to modern (Holocene) conditions. However, significant differences are observed during cold intervals, with higher relative flow speeds inferred for the shallow component of the WBUC ( 2 km depth) during all cold "stadial" intervals (including Heinrich Stadial 6), and a substantial weakening of the deep component ( 3–4 km) during full glacial conditions. Our results therefore reveal that the onset of full glacial conditions was associated with a regime shift to a shallower mode of circulation (involving Glacial North Atlantic Intermediate Water) that was quantitatively distinct from preceding cold stadial events. Furthermore, our chemical proxy data show that the physical response of the WBUC during the last glacial inception was probably coupled to basin‐wide changes in the water‐mass composition of the deep Northwest Atlantic. Key Points: The Western Boundary Undercurrent is examined across the MIS 5a/4 transition Changes in flow speed structure are linked to abrupt climate change events Full glacial conditions are associated with a shallower mode of circulation